Research on anchorages of the structural strengthening system with prestressed CFRP strips - Paśko, Paulina; Piątek, Bartosz; Siwowski, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The CFRP composite materials due to their excellent mechanical properties are more often used in civil engineering. In recent more than ten years has been observed e.g. much wider application of CFRP strips in structural strengthening. The research on this subject clearly showed the advantages of prestressed strips application in contrast to passive one. The CFRP utilization is much more effective in terms of strength and economy. However, the system effectiveness depends on reliability of anchoring used for prestressed strips. The main goal of the research presented in the paper was to develop a new, innovative, effective and reliable anchoring system for CFRP strips. The achievement of quite high carrying capacity of new anchorages was able thanks to combining friction, bonding and rivet clamping in one CFRP-steel joint. The research results revealed the effectiveness of new anchoring system with carrying capacity level of about 70% of the CFRP ultimate tensile strength.